2014
DOI: 10.1080/00222895.2014.967655
|View full text |Cite
|
Sign up to set email alerts
|

Learning, Motor Skill, and Long-Range Correlations

Abstract: Long-range correlations have been evidenced in a number of experiments, generally using overlearned and overpracticed tasks. The authors hypothesized that long-range correlation could represent the byproduct of learning. They analyzed the series of periods produced by a group of expert and a group of novices during prolonged trials on a ski simulator. Results showed a very low variability in expert's series, as compared to novices. Fractal analyses showed that fluctuations were significantly more structured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Introduction: A relatively new finding relevant to sports is that optimal performance and well-trained behavior is reflected in patterns of high-frequency and low-amplitude fluctuations nested within low-frequency and high-amplitude fluctuations, called pink noise (e.g., Wijnants et al, 2009;Wijnants et al, 2012). Studies with cyclists, long-distance runners, skiers, and rowers, have consistently demonstrated pink noise in the athletes' performance time series (e.g., Hoos et al, 2014;Nourrit-Lucas et al, 2015). Moreover, recent studies revealed that higher-skilled rowers (Den Hartigh et al, 2015) and skiers (Nourrit-Lucas et al, 2015) demonstrated more prominent patterns of pink noise than less-skilled athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction: A relatively new finding relevant to sports is that optimal performance and well-trained behavior is reflected in patterns of high-frequency and low-amplitude fluctuations nested within low-frequency and high-amplitude fluctuations, called pink noise (e.g., Wijnants et al, 2009;Wijnants et al, 2012). Studies with cyclists, long-distance runners, skiers, and rowers, have consistently demonstrated pink noise in the athletes' performance time series (e.g., Hoos et al, 2014;Nourrit-Lucas et al, 2015). Moreover, recent studies revealed that higher-skilled rowers (Den Hartigh et al, 2015) and skiers (Nourrit-Lucas et al, 2015) demonstrated more prominent patterns of pink noise than less-skilled athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with cyclists, long-distance runners, skiers, and rowers, have consistently demonstrated pink noise in the athletes' performance time series (e.g., Hoos et al, 2014;Nourrit-Lucas et al, 2015). Moreover, recent studies revealed that higher-skilled rowers (Den Hartigh et al, 2015) and skiers (Nourrit-Lucas et al, 2015) demonstrated more prominent patterns of pink noise than less-skilled athletes. In addition to pink noise in individual performance, it has recently been shown that two people who perform a task together tend to match the fractal patterns of their behavioral time series.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, fractal properties in physiology seem to disappear with aging (21), which is reversible to some extent (14), and disease (16,39). Fractal complexity is also a marker of learning skills (31,40,41).…”
Section: Variability In Physiologymentioning
confidence: 99%
“…The presence of fractal dynamics appears to be the rule rather than the exception in physiology. The phenomenon, also referred to as long-range correlations, long-range dependence, long-term memory, or pink noise (15,31), is widespread in humans across brain activity (3), autonomic control (21,33), cognitive performance (8,39), and motor behavior (5,6,15). The term "1/f noise" is also frequent (6,8,39).…”
Section: Fractal Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation